2001
DOI: 10.1074/jbc.m010774200
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein Does Not Protect Cells against Cytolysis Induced by Pore-forming Proteins

Abstract: P-glycoprotein (P-gp) is an ATP-dependent drug pump that confers multidrug resistance (MDR). In addition to its ability to efflux toxins, P-gp can also inhibit apoptosis induced by a wide array of cell death stimuli that rely on activation of intracellular caspases for full function. We therefore hypothesized that P-gp may have additional functions in addition to its role in effluxing xenotoxins that could provide protection to tumor cells against a host response. There have been a number of contradictory repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…We have recently reported that P-gp was unable to confer resistance to cell death by pore-forming proteins such as complement, perforin and pneumolysin. 38 CEM-GFP, CEM-P-gp WT , CEM-P-gp MM-3 and CEM-P-gp MM-32 cells were treated with normal rabbit serum as a source of complement and cell lysis was assessed by 51 Cr release (Figure 6d). Endogenous CEM cell-reactive antibodies within the rabbit serum were shown by flow cytometry to bind equivalently to all four transduced cell lines (data not shown) and enabled activation of the classical complement pathway and the rapid induction of cell lysis.…”
Section: Cem-p-gpmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that P-gp was unable to confer resistance to cell death by pore-forming proteins such as complement, perforin and pneumolysin. 38 CEM-GFP, CEM-P-gp WT , CEM-P-gp MM-3 and CEM-P-gp MM-32 cells were treated with normal rabbit serum as a source of complement and cell lysis was assessed by 51 Cr release (Figure 6d). Endogenous CEM cell-reactive antibodies within the rabbit serum were shown by flow cytometry to bind equivalently to all four transduced cell lines (data not shown) and enabled activation of the classical complement pathway and the rapid induction of cell lysis.…”
Section: Cem-p-gpmentioning
confidence: 99%
“…Complement treatment of cells and 51 chromium release assays were performed as previously described. 38 P-gp reversal assays were performed by preincubating cells in anti-P-gp monoclonal antibodies (16 mg/ml UIC2 (Immunotech, Marseille, France) or 100 mg/ml MRK16) for 1 h prior to addition of 50 ng/ml vincristine. Samples were then incubated for 24 h at 371C and trypan counted as above.…”
Section: Cytotoxicity and Viability Assaysmentioning
confidence: 99%
“…Five other physiological functions have been attributed to the drug-transporting Pgps (151): transport of cytokines, particularly interleukin 2 (IL-2), IL-4, and gamma interferon (IFN-␥) (160, 161); increased self-renewal and decreased differentiation of hematopoietic stem cells (162); migration of antigen-presenting dendritic cells and T lymphocytes (163); inhibition of alloantigen-dependent, but not mitogen-dependent, T-cell activation (164); and inhibition of apoptosis [reviewed in (151)], but not cytolysis by pore-forming proteins (165,166). The evidence for these physiological functions rests mainly on the effects of Pgp inhibitors, gross overexpression of a Pgp gene, or the effects of anti-Pgp antibodies, and remains the subject of lively discussions (167).…”
mentioning
confidence: 99%
“…8 This effect can be achieved via generation of membranotropic intracellular metabolites such as ROS. The toxicity of ROS is not confined to the break of biological membranes (necrosis); oxygen burst-induced damage of macromolecules can trigger apoptotic cascades.…”
Section: P-glycoprotein As a Therapeutic Target: Good Newsmentioning
confidence: 99%